What Was the Wild West? - Pascal, Janet B.; Marchesi, Stephen (New York, New York : Grosset & Dunlap, 2017)
The West was at its wildest from 1865 to 1895, when territories west of the Mississippi River remained untamed and lawless. Famous for cowboys, American Indians, lawmen, gunslingers, pioneers, and prospectors, this period in US history captures the imagination of all kids and now is brought vividly to life.
Includes bibliographical references (page 106)
Keywords: Frontier and pioneer life -- 19th century -- Juvenile literature -- West (U.S.); West (U.S.) -- 19th century -- History -- Juvenile literature; Illustrated works